Performance Determinants in Short (68 km) and Long (121 km) Mountain Ultra-Marathon Races - Gatterer, Hannes; Rauch, Simon; Procter, Emily; Strapazzon, Giacomo; Schenk, Kai (Sportverletzung · Sportschaden, 2020)
Background Standard performance parameters measured during a laboratory test have been shown to be related to mountain ultra-marathon performance up to a competition length of 75 km. It is not known if a similar relationship exists for longer races.Objective This study aimed to investigate the association between laboratory-based performance parameters and performance times in a short (68 km) and a long (121 km) mountain ultra-marathon.Materials and Methods Eleven male finishers of the short race and seven male finishers of the long race were investigated. Participants performed an incremental exercise test to exhaustion in the 2 weeks prior to the event. During the event, the heart rate was monitored and finishing times were registered.Results The maximal oxygen consumption and the oxygen uptake at the ventilatory thresholds 1 and 2 were related to performance time during the short run (~12h; r = –0.764 up to r = –0.782; p < 0.05), but there was no correlation during the long race (~28h; r = –0.107 to 0.357; p > 0.05).Conclusions This study shows that physical fitness parameters established in a laboratory setting determine competition completion times in ultra-mountain marathon events lasting for ~12 h. During longer races, i. e. ~28 h, other factors not established in the present investigation, such as experience, race strategy, coping with pain and fatigue resistance, may be important for performance.
Keywords: trail running; eccentric exercise; fatigue; exercise testing; muscle damage; endurance running